STUDENTS’ LEARNING ATTITUDES AS IMPACT OF ONLINE LEARNING MATERIALS - Masda Surti Simatupang; Erni Murniarti; Ramot Peter (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study focused on the online learning system, which was nowadays of millennial students’ choices of learning preferences comparing to regular classes. The research aimed to reveal how students understand the learning materials, what they prepared if they did not comprehend the materials, and the handicaps they encountered during the online class. It was qualitative research where the results were explained using words, not statistics. The participants were 29 online students who took ’English Professional’ at Binus University online class. After joining the English course for one term or 16 weeks, they were required to answer questions at the end of the period. The results showed that most online students (40%) read and understood the materials provided in the Learning Management System (LMS). If they did not understand the materials, the majority (47%) searched the internet. The handicap of online learning was time management between study and work (35%).